2019
DOI: 10.31820/pt.28.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Croatian Adaptation of the Revised Reading the Mind in the Eyes Test (RMET)

Abstract: The aim of this research was to translate and adapt the revised version of the "Reading the mind in the eyes test" (Baron-Cohen et al., 2001) to the Croatian language, and to provide preliminary data on its reliability, factor structure and convergent validity in a healthy population of Croatian students. After translation and adaptation, the Croatian version of the RMET was administered to 146 undergraduate and graduate students (84 female and 62 male participants). Together with the RMET, we administered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Despite the near universal practice of calculating a single sum score for the 36-item Eyes Test, there are two key pieces of evidence that the structural properties of Eyes Test scores vary across samples and that the interpretation of sum scores is not always supported. First, factor analysis studies spanning multiple language versions of the Eyes Test have reported poor unidimensional model fit (e.g., Dordevic et al, 2017;Higgins, Ross, Langdon, & Polito, 2023a;Olderbak et al, 2015;Redondo & Herrero-Fernández, 2018;Topić & Kovačević, 2019), and it has even been found that the factor structure of Eyes Test scores for different ethnic and linguistic groups within the same country can vary (Van Staden & Callaghan, 2021). Second, a recent meta-analysis identified substantial variation in the internal consistency estimates of Eyes Test scores across samples, with half falling below the level conventionally taken to be acceptable (Kittel, Olderbak, & Wilhelm, 2022).…”
Section: Competing Interest Nonementioning
confidence: 99%
“…Despite the near universal practice of calculating a single sum score for the 36-item Eyes Test, there are two key pieces of evidence that the structural properties of Eyes Test scores vary across samples and that the interpretation of sum scores is not always supported. First, factor analysis studies spanning multiple language versions of the Eyes Test have reported poor unidimensional model fit (e.g., Dordevic et al, 2017;Higgins, Ross, Langdon, & Polito, 2023a;Olderbak et al, 2015;Redondo & Herrero-Fernández, 2018;Topić & Kovačević, 2019), and it has even been found that the factor structure of Eyes Test scores for different ethnic and linguistic groups within the same country can vary (Van Staden & Callaghan, 2021). Second, a recent meta-analysis identified substantial variation in the internal consistency estimates of Eyes Test scores across samples, with half falling below the level conventionally taken to be acceptable (Kittel, Olderbak, & Wilhelm, 2022).…”
Section: Competing Interest Nonementioning
confidence: 99%
“…Despite the near universal practice of calculating a single sum score for the 36-item Eyes Test, there are two key pieces of evidence that the structural properties of Eyes Test scores vary across samples and that the interpretation of sum scores is not always supported. First, factor analysis studies spanning multiple language versions of the Eyes Test have reported poor unidimensional model fit (e.g., Dordevic et al, 2017; Higgins, Ross, Langdon, & Polito, 2023a; Olderbak et al, 2015; Redondo & Herrero-Fernández, 2018; Topić & Kovačević, 2019), and it has even been found that the factor structure of Eyes Test scores for different ethnic and linguistic groups within the same country can vary (Van Staden & Callaghan, 2021). Second, a recent meta-analysis identified substantial variation in the internal consistency estimates of Eyes Test scores across samples, with half falling below the level conventionally taken to be acceptable (Kittel, Olderbak, & Wilhelm, 2022).…”
mentioning
confidence: 99%
“…The Reading the Mind in the Eyes Test is an internationally recognized single-picture stimuli method of assessing ToM (Baron-Cohen et al, 2001 ; Jankowiak-Siuda et al, 2016 ; Kotrla Topić & Perković Kovačević, 2019 ; Miguel et al, 2017 ; Morandotti et al, 2018 ). As the original version of the RMET was being revised, a child version (RMET-C) was developed to parallel the 36-item revised adult version (RMET-A).…”
mentioning
confidence: 99%